Children's temporal reasoning. [article]. - Ge, Fang
The purpose of this study is to explore children's reasoning based on temporal relations, such as: "a before b, b before c, d while b, c while e. What is the relation between d and e?" three versions of each problem were constructed in the following way: One-model problem based on four premises with irrelevant first premise; One model problem based on four premise with transitive relation; one model problem based on two premises; Multiple-model problem based on four premises. All the problems have valid answer. The subjects were tested individually. 54 pupils aged 7 to 11 from primary schools participated voluntarily in the experiment. The subjects' tasks were to answer a series of questions based on the information about the order of events given in the preceding assertions. The results indicated: 1)The percentage of correct inferences increased with age; 2)Two-premise problem yielded fewer errors than four-premise problems; 3)One-model problems with irrelevant first premise led to more errors than one-model problem with transitive relation; 4)there were no significant differences between one-model problem and multiple-model problem. The conclusion was that the number of models seems not to be a critical factor which affected children's temporal reasoning.